A desconsideração da personalidade jurídica no direito tributário: dogmática e análise da jurisprudência brasileira - Silva, Rodrigo Martins da (2015)
This paper intends to analyse the possibility of applying the lifting of the corporate veil theory to the tax Law. Starting at the basic definitions, the paper‟s objective is to demonstrate the main aspects and fundaments of this theory in order to apply and test them in the subsystem of tax Law, considering its material and procedural particularities. Concluding that it is possible to apply the lifting of the corporate veil to the tax Law, after analysing and conjugating various doctrinaire and jurisdictional understandings, this paper finally aims at offering a critical and comparative analysis between the lifting of the corporate veil and similar institutions. It constitutes a multidisciplinary paper that aggregates institutions and doctrinaire concepts belonging to various Law subsystems, such as the civil, the commercial, the procedural, and mainly, the tax Law, confronting them with decisions taken by Brazilian courts, specially the Superior Court of Justice